2021
DOI: 10.1186/s40537-021-00459-1
|View full text |Cite
|
Sign up to set email alerts
|

Text based personality prediction from multiple social media data sources using pre-trained language model and model averaging

Abstract: The ever-increasing social media users has dramatically contributed to significant growth as far as the volume of online information is concerned. Often, the contents that these users put in social media can give valuable insights on their personalities (e.g., in terms of predicting job satisfaction, specific preferences, as well as the success of professional and romantic relationship) and getting it without the hassle of taking formal personality test. Termed personality prediction, the process involves extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 30 publications
1
27
1
Order By: Relevance
“…Moreover, they have concatenated the deep semantic features with the statistical linguistic features obtained directly from the text posts, and have fed them into a regression model to predict the Big Five personality traits' labels. Exploiting the embedding methods abilities, in their study Christian et al [17] have suggested a multi model deep learning architecture for personality prediction which was combined with various pre-trained language model including BERT, RoBERTa, and XLNet as a feature extraction method on social media text. The main idea behind their investigations was that, since the common deep learning models such as recurrent neural networks (RNNs) and LSTMs suffer from some drawbacks that are defeated using embedding methods, the embedding methods practically outperform them.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, they have concatenated the deep semantic features with the statistical linguistic features obtained directly from the text posts, and have fed them into a regression model to predict the Big Five personality traits' labels. Exploiting the embedding methods abilities, in their study Christian et al [17] have suggested a multi model deep learning architecture for personality prediction which was combined with various pre-trained language model including BERT, RoBERTa, and XLNet as a feature extraction method on social media text. The main idea behind their investigations was that, since the common deep learning models such as recurrent neural networks (RNNs) and LSTMs suffer from some drawbacks that are defeated using embedding methods, the embedding methods practically outperform them.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the last few years, we have witnessed a considerable rise in text-based APP, that have used embedding methods to transfer the text elements to a more meaningful space (rather than character space), in favor of a better exploitation of computational methods [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…A wide diversity of contributions has been published on deep learning-based APP, each of which has a distinct methodology. During last years, an increasing number of studies have investigated the application of embedding methods to transfer the text elements from a textual space to a real valued vector space [14][15][16]18]. The authors in [14], integrated traditional psycholinguistic features such as Mairesse, SenticNet, NRC Emotion Intensity Lexicon, and VAD Lexicon (a lexicon of over 20,000 English words annotated with their valence, arousal and dominance scores), with several language model embeddings, including Bidirectional Encoder Representation from Transformers (BERT), ALBERT (A Lite Biomedical BERT) and RoBERTa (A Robustly Biomedical BERT Approach) to predict personality from the Essays Dataset in Big Five model.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At last, they have used three different models (CNN, GRU and LSTM) to perform final predictions on MBTI and Big Five model. In an attempt to predict users' personality in social media, Christian et al [16] proposed a multi model deep learning system based on multiple pre-trained language model, including: BERT, RoBERTa, and XLNet as the features extraction methods. Similarly, they also believed that the existing algorithms suffers from the absence of context information.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Over the years, it has received much attention; while some studies have applied a combination of linguistic features and machine learning methods [ 6 9 ], some others have focused solely on the machine (deep) learning methods [ 10 13 ]. In the last few years, we have witnessed a considerable rise in text-based APP, which have used embedding methods to transfer the text elements to a more meaningful space (rather than character space), in favor of better exploitation of computational methods [ 14 17 ].…”
Section: Introductionmentioning
confidence: 99%